Direct Utilization of Organic Nitrogen by Phytoplankton and Its Role in Nitrogen Cycling Within the Southern California Bight - Morando, Michael; Capone, Douglas G. (Frontiers in Microbiology, 2018)
The new production model attempts to quantify the amount of organic material exported from surface waters based on the form of nitrogen (N) being utilized. Dissolved organic N (DON) is rarely assessed during such investigations and even less is understood about the organisms involved in these different transformations within the complex N cycle. Stable isotope probing (SIP) and uptake activity measurements were combined to investigate the dynamics of new and regenerated production during the spring within the Southern California Bight (SCB). We examined the uptake and assimilation of several nitrogenous substrates at several depths to quantify these processes and identify the active communities across all three domains of life that are driving each transformation. Several reoccurring members closely related to the eukaryotic diatom Chaetoceros, dominated assimilation of NO3- and urea through the water column, and contributed greatly to the overall production. Prokaryotic growth was predominantly carried out through NH4+ assimilation with transitions from Flavobacteria to Rhodobacteraceae and Marine Group II Euryarchaeota to Marine Group I Thaumarchaeota with increasing depth for bacterial and archaeal clades respectively. Only urea uptake and SIP activity correlated with each other, likely demonstrating that cellular transport and incorporation of urea were coupled. SIP was therefore able to identify the organisms primarily responsible for urea cycling at each depth during this investigation. The role of diatoms within high nutrient areas are well defined but their part in DON cycling in highly stratified regimes is less well understood. Here we demonstrate their ability to efficiently scavenge urea in situ, allowing certain diatoms to outcompete the rest of the community. This diversion of DON away from the trophically inefficient microbial loop directly back into the larger, particle forming populations would alter the current view of microbial food webs. This proposed ‘phytoplankton shunt’ of organic material could potentially enhance the biological pump by mitigating losses due to trophic transfers while increasing DON flux due to ballasting. Our results provide unique biogeochemical and ecological insight into the dynamics and diversity of N cycling and the organisms involved within the surface waters of the SCB.